Resistensi Antibiotik Terhadap Bakteri Escherichia coli yang Diisolasi dari Peternakan Ayam Pedaging di Kabupaten Subang, Jawa Barat (ANTIBIOTIC RESISTANCE TO ESCHERICHIA. COLI ISOLATED FROM BROILER FARMS IN SUBANG DISTRICT, WEST JAVA PROVINCE) - Niasono, Aji Barbora; Latif, Hadri; Purnawarman, Trioso (Jurnal Veteriner, 2019)
Antibiotic resistance in avian bacterial pathogens is a common problem in the Indonesia poultry industry. The present study aimed to provide information on the present status of antibiotic resistance in Escherichia coli (E. coli) from a broiler farm environment. The research method uses a cross sectional study with a stratified random sampling pattern. E. coli was collected from litter using boot swab method at the broiler house farms in Subang District. E. coli isolates (n = 74) were obtained from 74 samples of boot swabs. The sample was isolated and identified morphologically and biochemically using the IMVIC test to obtain E. coli isolates. The test was followed by a sensitivity test for nine antibiotics, namely tetracycline, sulfamethoxazole, trimethoprim, ampicillin, nalidixic acid, ciprofloxacin, enrofloxacin, gentamicin and chloramphenicol by using the agar dilution method. The interpretation of the results of this sensitivity test refers to the Clinical and Laboratory Standards Institute CLSI VET01S (2015) and CLSI M100 (2018). Measurement of the level of knowledge is done using a structured questionnaire that has been tested for validity and reliability. E. coli was isolated from 74 samples of boot swab. 93.2% of E. coli samples were found to be MDR with the highest prevalence in four types of antibiotics at 40.5%. The most common resistances observed were against tetracycline 97.3%, sulfamethoxazole 87.8%, trimethoprim 74.3%, ampicillin 68.9%, nalidixic acid 64.8%, ciprofloxacin 45.9%, enrofloxacin 40.5%, gentamicin 28.4% and chloramphenicol 10.8%. The findings of this study revealed the high level of antibiotic resistance in broiler environment is worrisome and have negative implications for human and animal health.